2021
DOI: 10.1007/s00216-021-03311-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in drugs of abuse metabolism studies for mass spectrometry–based analytical screening procedures

Abstract: The still increasing number of drugs of abuse, particularly the so-called new psychoactive substances (NPS), poses an analytical challenge for clinical and forensic toxicologists but also for doping control. NPS usually belong to various classes such as synthetic cannabinoids, phenethylamines, opioids, or benzodiazepines. Like other xenobiotics, NPS undergo absorption, distribution, metabolism, and excretion processes after consumption, but only very limited data concerning their toxicokinetics and safety prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Wagmann et al also found the zebrafish and zebrafish larvae to be a promising and emerging topic in metabolism studies of NPS but also concluded that establishing and maintaining a zebrafish culture platform is expensive and experienced personnel are required (Wagmann et al, 2021). However, no matter which model—adult zebrafish or larvae—will be used, there is still a need for standardization of the model and to extent the knowledge of similarity with human metabolism (de Souza Anselmo et al, 2018).…”
Section: Toxicokinetics Of Nps Studied By Using Zebrafish Larvaementioning
confidence: 99%
“…Wagmann et al also found the zebrafish and zebrafish larvae to be a promising and emerging topic in metabolism studies of NPS but also concluded that establishing and maintaining a zebrafish culture platform is expensive and experienced personnel are required (Wagmann et al, 2021). However, no matter which model—adult zebrafish or larvae—will be used, there is still a need for standardization of the model and to extent the knowledge of similarity with human metabolism (de Souza Anselmo et al, 2018).…”
Section: Toxicokinetics Of Nps Studied By Using Zebrafish Larvaementioning
confidence: 99%
“…While in silico models exist to assist with the prediction of these properties, 9,10 in vitro experiments 11,12 and more so in vivo studies are imperative to fully confirm the behavior of a new substance. 13 Several alternatives to in vitro models have been proposed, such as human liver microsomes (HLM), human liver S9 fraction (HLS9), primarily cytochrome P450 (CYP) and UDP-glucuronosyltransferase (UGT) isozymes, and primary human hepatocytes (PHH). 14 On the other hand, traditional in vivo tools to study metabolism of NPS include rats, 15 the most commonly used mammalian model, chimeric mice with a humanized liver, 16 pig, 17 and zebrafish and zebrafish larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from adult zebrafish, zebrafish larvae have been used in metabolism studies, because larvae provide the main benefits of adult individuals but are not considered as animals until 5-day postfertilization (dpf) according to the European Directive 2010/63/EU, and thus, experiments with zebrafish larvae do not require an ethical approval in the EU if they are completed within 5 days after fertilization. 13 Other advantages of zebrafish and zebrafish larvae models are related to the high degree ofphysiological and genetic homology to humans. 20 According to Howe et al, zebrafish genome, fully sequenced, shows orthologues corresponding to $82% of disease-related genes in humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations